2018
DOI: 10.25035/ijare.11.01.02
|View full text |Cite
|
Sign up to set email alerts
|

"We Just Treat Everyone the Same": LGBTQ Aquatic Management Strategies, Barriers and Implementation

Abstract: This study examined the management of aquatic venues in a number of areas (facilities, programming, human resource management, marketing, policies) as it pertains to LGBTQ participants and participation. The study utilized in-depth semi-structured interviews with 16 aquatic managers to examine steps that are currently being taken (or lack thereof) when it comes to creating environments that are perceived to be open, or closed, to LGBTQ participants. A grounded theorybased process of data collection and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The management of recreation facilities and programs has an impact on numerous stakeholders including the participants and employees. While diversity and inclusion is a goal often forwarded by collegiate recreation organizations and associations (Kaltenbaugh et al, 2017;Lower-Hoppe et al, 2019;Patchett & Foster, 2015), there is still critical work needed given ongoing research findings of inequitable experiences for recreation participants (Carter-Francique, 2011;Griffith et al, 2011;Schwartz & Corkery, 2011;Smith et al, 2007) and a lack of competency among recreation staff (Anderson et al, 2018;Kaltenbaugh et al, 2017).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of recreation facilities and programs has an impact on numerous stakeholders including the participants and employees. While diversity and inclusion is a goal often forwarded by collegiate recreation organizations and associations (Kaltenbaugh et al, 2017;Lower-Hoppe et al, 2019;Patchett & Foster, 2015), there is still critical work needed given ongoing research findings of inequitable experiences for recreation participants (Carter-Francique, 2011;Griffith et al, 2011;Schwartz & Corkery, 2011;Smith et al, 2007) and a lack of competency among recreation staff (Anderson et al, 2018;Kaltenbaugh et al, 2017).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…As noted by the driving and resisting forces of the IFCD (Doherty et al, 2010), there are likely ways in which collegiate recreation practitioners do not engage or actively resist engagement in diversity and inclusion efforts. While some barriers have already been found (Anderson et al, 2018;Kaltenbaugh et al, 2017), further examination of resistance would benefit the field by illuminating opportunities to develop more effective approaches to counteract active and passive opposition to social justice.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Aquatic managers within this study also reported that inclusion efforts are often made at the programming and departmental levels, but the efforts are generally reactive in nature due to specific participant requests or are extremely general in nature (i.e., programming for “everyone”). These types of efforts, while laudable and common in other aquatic spaces (A. R. Anderson et al, 2018), can create some problematic environments.…”
Section: Discussionmentioning
confidence: 99%
“…While these spaces likely present fewer logistical barriers to students overall, identity-specific barriers to SM initiation have been relatively underexamined, particularly in contrast to varsity levels. Much of the recent literature in this area has engaged perspectives of recreational sports staff (Anderson et al, 2018(Anderson et al, , 2020 or has focused specifically on barriers to inclusion for transgender participants (Patchett & Foster, 2015). Examining the ways SM themselves describe navigating decisions about initiation and persistence in sports and physical activity is important to supporting today's college student body in sustaining healthy lifestyles.…”
Section: Introductionmentioning
confidence: 99%